Structured Mentoring as a Catalyst for Developing Professional Competencies Among University Students - Rojak, Jeje Abdul (Journal of Social Science Studies, 2024)
Mentoring in higher education has garnered increasing scholarly attention as a potential mechanism for fostering professional competencies among students. This literature-based study explores the theoretical foundations and empirical evidence surrounding structured mentoring programs and their capacity to enhance students’ preparedness for professional environments. Synthesizing works published across multiple academic traditions, this analysis identifies key factors that influence the efficacy of mentoring, including mentor-mentee alignment, emotional intelligence development, exposure to tacit knowledge, and institutional commitment. Findings indicate that mentoring fosters a range of competencies such as adaptive thinking, self-regulation, ethical reasoning, and cross-cultural communication. It also serves as a medium for identity construction and long-term professional formation. While the positive outcomes are promising, the study also identifies gaps in longitudinal validation, inconsistent assessment frameworks, and unequal access across student populations. This review concludes that mentoring must be integrated as a deliberate component of higher education strategy and not merely as an auxiliary service. Such integration demands investment in mentor preparation, evaluation systems, and cultural responsiveness to maximize its developmental potential. The paper offers conceptual clarity and practical insights for future program development and educational policy formulation.